Bioavailability and toxicity of silver nanoparticles: Determination based on toxicokinetic–toxicodynamic processes. (1st October 2021) - Gao, Yongfei; Wu, Weiran; Qiao, Kexin; Feng, Jianfeng; Zhu, Lin; Zhu, Xiaoshan
Highlights: The gradient Ag + simulated bulk dissolution but not intracellular dissolution of AgNP. The survival upon AgNP exposure was predicted by the total bodily Ag + concentration. AgNP toxicity was mainly due to enhanced extracellular and intracellular dissolution. The S9 fractions might cause PVP-AgNPs to lose the PVP coating and favor Ag + release. Abstract: Determining the bioavailability and toxicity mechanism of silver nanoparticles (AgNPs) is challenging as Ag + is continuously released by external or internal AgNP dissolution in the actual exposure system (regardless of the laboratory or the natural environment). Here a novel pulsed-gradient Ag + (AgNO3 ) exposure was conducted with zebrafish ( Danio rerio ) larvae to simulate dissolved gradient concentrations of Ag + from polyvinylpyrrolidone (PVP)-coated AgNPs. The accumulation and toxicity of the pulsed-gradient Ag + (AgNO3 ) and, in the meantime, the released Ag + from PVP-AgNPs were predicted using a toxicokinetic–toxicodynamic (TK–TD) model with obtained Ag + parameters. In order to further understand the possible mechanism of PVP-AgNP releasing Ag + in the body, subcellular fractions (S9) of zebrafish were also used to incubate with AgNPs in vitro to mimic the realistic in vivo scenarios. In the TK process, in vivo analysis showed that AgNPs released around twice as many Ag + into the body than were detected with a single Ag + pulse-exposure system; this was supported by evidence that subcellular S9 fractions might cause the PVP-AgNPs to lose the capping agent and favor Ag + release. In the TD process, toxicity (survival rate) was predicted by the total bodily Ag(I) concentration, suggesting that AgNP toxicity in larvae was mainly due to gradually released Ag + rather than AgNPs themselves. This study helps clarify the role of Ag + in AgNP toxicity and offers a novel framework by which to investigate the toxicity of metal nanoparticles and corresponding metal ions in biological systems. Graphical abstract: Image, graphical abstract